2016
DOI: 10.11113/jt.v78.8145
|View full text |Cite
|
Sign up to set email alerts
|

BLOOD GLUCOSE LEVEL AND LIPID PROFILE OF ALLOXAN–INDUCED DIABETIC RATS TREATED WITH NA-ALGINATE FROM SEAWEED Turbinaria ornata (Turner) J.Agardh

Abstract: Diabetes mellitus (DM) is a metabolic disorder due to insulin deficiency, insulin resistance or inability of β-cells of pancreas to produce insulin. This study was aimed to evaluate the effects of Na-alginate from Turbinaria ornata (Turner) J.Agardh on glucose level and lipid profile in alloxan-induced diabetic rats. Na-alginate was extracted from T. ornata then analyzed by TLC and FTIR. In vivo test was performed on alloxan monohydrate induced diabetic rats. In vivo parameters evaluated were body weight, bloo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 22 publications
1
16
0
Order By: Relevance
“…As observed in the previous study, alginate could decrease fasting plasma glucose in diabetic rats (7).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…As observed in the previous study, alginate could decrease fasting plasma glucose in diabetic rats (7).…”
Section: Discussionsupporting
confidence: 77%
“…Its chain is made of homopolymeric regions of β-D-mannuronic acid and α-L-guluronic acid. The previous study approved that Na-alginate (at 600 mg•kg − 1 ) increased weight of diabetic rat significantly comparing to normal control, and decreases pre-prandial and postprandial glucose (7). Another study indicated that α-Lguluronic acid had immunomodulatory effect by decrease the expression of Toll-like receptor 2 (TLR2) and Nuclear Factor-kB (NF-kB)genes in Common variable immunodeficiency (CVID) patients (8).…”
Section: Introductionmentioning
confidence: 99%
“…They are categorized based on their pigments content, morphological and anatomical attributes into three divisions which are red algae (Rhodophyceae), brown algae (Phaeophyceae) and green algae (Chlorophyceae) (Manivannan et al, 2009). There is an excessive interest for screening helpful medications from marine algae as they contain bioactive compounds, e.g., polysaccharides, pigments, proteins, lipids, peptides, minerals and vitamins (Husni et al, 2016). They have diversified biological activities, such as anti-hypertensive, anti-hyperlipidemic, anti-coagulant, apoptotic activities (Lee & Han, 2012), antioxidant, anti-inflammatory and anticancer (Khalid et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…They have diversified biological activities, such as anti-hypertensive, anti-hyperlipidemic, anti-coagulant, apoptotic activities (Lee & Han, 2012), antioxidant, anti-inflammatory and anticancer (Khalid et al, 2018). They also could play an important role in the control of diabetes (Unnikrishnan et al, 2015) by regulation of glucose-instigated oxidative stress and suppression of starch hydrolyzing enzymes (Husni et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…), antidiabetes and anti‐obesity (Husni et al . ). Besides these, oral administration of alginate from brown seaweed, Sargassum sp.…”
Section: Introductionmentioning
confidence: 97%